General Analysis of a Loop Antenna Located on a Uniaxial Metamaterial Cylinder - Anna S. Zaitseva; Alexander V. Kudrin; Tatyana M. Zaboronkova (IEEE Access, 2022)
The general problem of determining the electrodynamic characteristics of a circular loop antenna located coaxially on the surface of a metamaterial cylinder is studied using the integral equation method. The antenna has the form of a perfectly conducting, infinitesimally thin, narrow strip coiled into a ring and is excited by a given time-harmonic voltage. The cylinder is assumed to be filled with a uniaxial metamaterial and surrounded by an isotropic magnetodielectric. Integral equations for azimuthal harmonics of the antenna current are derived and solved in the cases where the normal waves of the metamaterial inside the cylinder have either hyperbolic or nonhyperbolic dispersion. Based on the solutions of these equations, the current distribution and input impedance of the antenna are found in closed form. The behavior of the antenna characteristics as functions of the metamaterial parameters is discussed.